Heterointerface Effect in Accelerating the Cathodic Oxygen Reduction for Intermediate-Temperature Solid Oxide Fuel Cells - Meng, Yu; Zhu, Xiaofei; Meng, Jiao; Bai, Jinghe; Chen, Ruyi; Zhou, Defeng; Wang, Ning; Tian, Dan (Frontiers in Chemistry, 2022)
A solid-state mixing method was adopted to prepare a new Pr0.8Sr0.2Fe0.7Ni0.3O3-δ-Pr1.2Sr0.8Fe0.4Ni0.6O4+δ (PSFN113-214) composite cathode oxide for the solid oxide fuel cells (SOFCs). Herein, heterointerface engineering was investigated for the performance enhancement. It was found that the oxygen vacancy content could be increased by mixing the PSFN214 with PSFN113, which gave rise to the formation of a heterostructure, and resulted in the promotion of oxygen ion transport as well as the specific surface area. The optimum mixing ratio 5:5 resulted in the highest oxygen vacancy content and the largest specific surface area, indicating the strongest interface effect. Polarization resistance of PSFN113-214 (5:5) was 0.029 Ω·cm2 at 800 °C, which was merely 24 % of PSFN113 and 39 % of PSFN214. The corresponding maximum power density was 0.699 W·cm-2, which was nearly 1.44 times of PSFN113 and 1.24 times of PSFN214. Furthermore, the voltage attenuation rate after 100 h was merely 0.0352% h-1. Therefore, the new PSFN113-214 composite could be a prospective cathode oxide for SOFCs.